Applied linguistics as a manifestation of exo-, meso- and endo-symbiosis - Puppel, Stanisław (Glottodidactica, 2016)
An assumption is made that applied linguistics may be viewed as an outcome of an interplay of a dichotomy of endogenous and exogenous symbionts, mediated by important mesogenous symbionts acting jointly within the domain of language and communication. All of them form a system of bifurcations which may generally be called ‘a flow tool-language design’ or The Bifurcational Model of Symbiosis (BiMoS). In this model, bifurcations form a ‘grammar of bifurcations’ whose power is symbiotic in the overall functioning of language. Furthermore, the occurrence of the above mentioned types of symbionts on the language side allows for a division of ‘linguolabourese’ (or the whole ‘life of language’ as opposed to ‘instrumentolabourese’, or the whole ‘life of tools’) into three more or less distinct and interconnected areas of symbiosis: the exogenous area, the mesogenous area, and the endogenous area, respectively. The afore mentioned areas further justify a division of linguistics into three respective types: exogenous (exo-) linguistics, mesogenous (meso-) linguistics, and endogenous (endo-) linguistics. Their subdomains of interest vary but are highly interconnected, blended and synergistic. Applied linguistics is viewed here as belonging predominantly to (or taking theoretical and practical interest in) the mesogenous and endogenous areas of linguolabourese, though it is strongly supported by the underlying exogenous area.